Ethnic Mixing and Tolerance in Urban Kenya: A Case Study of Mathare Informal Settelment in Nairobi City - Stellamaries Kyuvi; Charles Nzioka; Elias O. Ayiemba (European Scientific Journal, ESJ, 2023)
For any multi-ethnic society, tolerance is regarded as an integral element for social, economic, and political stability of the nation. Today, majority of the multi-ethnic nations in Africa still face the challenge on how to promote ethno-cultural tolerance and acceptance among the diverse populations. As a result, many African nations are entangled in inter-state conflicts and civil wars related to ethnic differences that pose a dilemma on whether to promote ethnic pluralism or not. In this study we examined whether ethnic mixing in the city can be a potential tool for promoting ethnic tolerance and peaceful co-existence, which can then be diffused to the rural regions and subsequently to the whole nation. The study adopted integrative study design that allowed use of mixed methods in the collection and analysis of data where eighty participants were interviewed in the initial survey and twenty-four in the in-depth interviews. Consistent with the contact theory the study found a compelling evidence that ethnic group exposure promotes cultural learning and out group accommodation, resulting to individuals who are more open to diversity. The study proposes ethnic mixing and the creation of ethnic diverse spaces as an alternative strategy for promoting ethnic understanding and nationhood. The paper is an excerpt from the author’s post-doctoral thesis on the role of rural-urban migrations in promoting ethnic integration in Kenya.